Self-regulated Learning and Digital Literacy: Relationship with Conceptual Understanding of Excretory System - Rusdi Rusdi; Rizhal Hendi Ristanto; Gabriellia Oktaviani Prabowo; Edi Sarwono (Universitas Pendidikan Indonesia, 2023)
Biology learning in the 21st century makes students have to understand concepts, including in excretory system learning. Self-regulated learning is the way students manage learning on their own, with digital literacy skills which should be maintained as students must control their use of technology and information in learning. This research aimed to analyze the relationship between self-regulated learning with the conceptual understanding of the excretory system, digital literacy with the conceptual understanding of the excretory system, then also the relationship between self-regulated learning and digital literacy as a whole with the conceptual understanding of the excretory system in a high school with a post-pandemic learning situation. This research was held for two months duration from March until April 2022 in SMAN 6 Jakarta, involving 94 students of class XI Science as samples. A descriptive correlational study was chosen as the method, while questionnaires and tests are used as instruments. The hypothesis test shows a multiple linear regression model in Ŷ=-12.495+0.345X1+0.680X2 with the model significance of 0.000 and 0.062 as relationship linearity, then concludes that there is a positive relationship which is significant and linear between self-regulated learning and digital literacy simultaneously with excretory system conceptual understanding.